Acute Myelopathy in Childhood - Giulia Bravar; Aphra Luchesa Smith; Ata Siddiqui; Ming Lim (MDPI AG, 2021)
Acute myelopathy presenting in childhood can be clinically classified based on the location of injury (with resulting spinal syndrome) or the cause (broadly traumatic or non-traumatic). Types of nontraumatic myelopathy include ischaemic, infectious, inflammatory, nutritional, and metabolic causes, some of which may be part of a systemic illness such as systemic lupus erythematosus or a demyelinating disease such as multiple sclerosis. Nonaccidental injury is an important consideration in cases of traumatic myelopathy, which may often be associated with other injuries. Assessment should include neuroimaging of the brain and spinal cord, with further investigations targeted based on the most likely differential diagnoses; for example, a child with suspected demyelinating disease may require specialist cerebrospinal fluid and serological testing. Management also will differ based on the cause of the myelopathy, with several of these treatments more efficacious with earlier initiation, necessitating prompt recognition, diagnosis, and treatment of children presenting with symptoms of a myelopathy. Important components of holistic care may include physiotherapy and occupational therapy, with multidisciplinary team involvement as required (for example psychological support or specialist bowel and bladder teams).